2008
DOI: 10.1073/pnas.0711551105
|View full text |Cite
|
Sign up to set email alerts
|

Scent evolution in Chinese roses

Abstract: The phenolic methyl ether 3,5-dimethoxytoluene (DMT) is a major scent compound of many modern rose varieties, and its fragrance participates in the characteristic ''tea scent'' that gave their name to Tea and Hybrid Tea roses. Among wild roses, phenolic methyl ether (PME) biosynthesis is restricted to Chinese rose species, but the progenitors of modern roses included both European and Chinese species (e.g., Rosa chinensis cv Old Blush), so this trait was transmitted to their hybrid progeny. The last steps of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 43 publications
(58 reference statements)
3
57
0
Order By: Relevance
“…gigantea and R. chinensis (Ku and Robertson 2003;Scalliet et al 2008; author's observations; Table 3). The four varieties of R. odorata are all lianas with five to seven leaflets and have the same scent compounds (Scalliet et al 2008). They mainly differentiate from one another by double-(semi-double) or single-petaled flowers, floral color, and the size of the petals (Ku and Robertson 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…gigantea and R. chinensis (Ku and Robertson 2003;Scalliet et al 2008; author's observations; Table 3). The four varieties of R. odorata are all lianas with five to seven leaflets and have the same scent compounds (Scalliet et al 2008). They mainly differentiate from one another by double-(semi-double) or single-petaled flowers, floral color, and the size of the petals (Ku and Robertson 2003).…”
Section: Discussionmentioning
confidence: 99%
“…gigantea (white to creamy-white flowers) and R. chinensis var. spontanea Ku and Robertson (2003), Scalliet et al (2008), and author's observation DMT 3,5-Dimethoxytoluene, TMB 1,3,5-trimethoxybenzene…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Rosa lucidissima has a unique character consisting of congested bristles on branchlets, pedicels and receptacles. Because this section includes important garden plants or wild ancestors of cultivated roses, research on this section has been prolific (see Meng et al, 2011;Scalliet et al, 2008;Scariot et al, 2006), but most studies focused on the garden roses or double-petaled varieties. In this study, we sampled all three wild taxa and double-petaled R. odorata (Andrews) Sweet var.…”
Section: Phylogeny Of Rosa Sections Chinenses and Synstylaementioning
confidence: 99%
“…2) involves two different OOMT1 and OOMT2 enzymes, which operate sequentially to catalyze the first and the second methylation step of orcinol, respectively . The evolution of OOMT1 from the duplicated OOMT2 gene most probably corresponds to an optimization of DMT biosynthesis in Chinese roses (Scalliet et al, 2008). A BLAST search of the genome of the highly homozygous PN40024 grapevine cultivar (Jaillon et al, 2007) identified a small family of four putative ROMT genes located on chromosome 12 (accession nos.…”
Section: Characterization Of a Novel Romt From Grapevinementioning
confidence: 99%